Acinetobacter spp in a Third World Country with Socio-economic and Immigrants Challenges - Iman Dandachi; Eid Azar; Ramzi Hamouch; Peter Maliha; Samah Abdallah; Elie Kanaan; Rebecca Badawi; Tamara Khairallah; Ghassan M Matar; Ziad Daoud (Journal of Infection in Developing Countries)
Introduction: In the last decade, Acinetobacter species have taken a major public health concern. This is mainly due the increased resistance to a wide range of antibiotics causing treatment challenges. In view of the constant population mobilization and the economic crisis that Lebanon is currently facing, it becomes a necessity to re-evaluate the real threat of Acinetobacter spp and its implication in the one health.